2018
DOI: 10.3390/fib6030054
|View full text |Cite
|
Sign up to set email alerts
|

Interface Characterization of Epoxy Resin Nanocomposites: A Molecular Dynamics Approach

Abstract: In polymer nanocomposites, the interface region between the matrix and the fillers has been identified as a key interaction region that strongly determines the properties of the final material. Determining its structure is crucial from several points of view, from modeling (i.e., properties prediction) to materials science (i.e., understanding properties/structure relationships). In the presented paper, a method for characterizing the interface region of polymer nanocomposites is described using molecular dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
(49 reference statements)
0
14
0
Order By: Relevance
“…Since the filler does not influence the bulk polymer region, the density fluctuations persist stable, and the related standard deviation (SD) takes a particular specific value. Considering this effect, Ezquerro et al., 2019, [122] presented a method for characterizing the interface region in triple‐walled carbon nanotubes (TWCNT) filled epoxy resin PNCs via density profiles in a more mathematical way, by calculating the accumulated standard deviation (ASD) profiles as given below. trueASD()d=dhρd-trueρ2n-14pt;h>d …”
Section: Molecular Evolution Of Interface Structure and Dynamics In Model Pncsmentioning
confidence: 99%
“…Since the filler does not influence the bulk polymer region, the density fluctuations persist stable, and the related standard deviation (SD) takes a particular specific value. Considering this effect, Ezquerro et al., 2019, [122] presented a method for characterizing the interface region in triple‐walled carbon nanotubes (TWCNT) filled epoxy resin PNCs via density profiles in a more mathematical way, by calculating the accumulated standard deviation (ASD) profiles as given below. trueASD()d=dhρd-trueρ2n-14pt;h>d …”
Section: Molecular Evolution Of Interface Structure and Dynamics In Model Pncsmentioning
confidence: 99%
“…Similarly to the typical empirical expressions adopted for heat transfer, only basic formula building-blocks (i.e., constant, multiplication, division, power) have been considered for the Eureqa fitting. As a result, the simulation results in Table A1 (configurations N. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] have been found to be best fitted (R 2 = 0.99, see Figure 4b) by the following expression:…”
Section: Resultsmentioning
confidence: 99%
“…Carbon fillers such as carbon nanotubes and graphene nanoribbons are often suggested as possible additives in composite materials. In fact, these materials show a remarkable combination of superior thermal [1][2][3][4], electrical [5][6][7], lubrication [8,9] and mechanical [10][11][12] properties, which have the potential to significantly enhance the performance of base materials. In particular, Polymer Nanocomposites (PNCs) with carbon nanofillers are currently employed in a broad variety of industries, such as the energy [13], aerospace [14], biomedical [15], electronics [16,17] and automotive ones [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the models were time integrated in the isobaric–isotherm ensemble (NPT, with the Nosé–Hoover thermobarostat) at 300 K and 1 atm, allowing all atoms to freely move, until reaching the plateau in density (which typically required between 0.5 and 1 ns). In the case of the epoxy resin, the cross-linking procedure, based on methods described in literature [ 14 , 20 ] and performed through consecutive steps of molecular dynamics simulations, was subsequently applied to obtain the desired cross-linking degree of 70%. At the abovementioned conditions used for the systems stabilizations, the PLA and EPO are in the glassy state, while the polypropylene is in the melting state, as reported in previous studies available in the literature [ 22 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Bigdeli and Fasano [ 12 ] and Mohammad Nejad et al [ 13 ] demonstrated, through reverse nonequilibrium molecular dynamics (RNEMD) simulations, that both geometry properties and the thermal boundary resistance between fillers affect significantly the overall thermal properties. In terms of the interactions between the matrices and the fillers, Sáenz et al [ 14 ] evaluated the interface thickness of composites based on epoxy resin and triple wall carbon nanotubes (TWCNT), by analyzing the density profile. Sun et al [ 15 ] calculated the interaction energy between epoxy resin and GO depending on the content of hydroxyl groups, identifying the range in which the interfacial energy seemed to decrease more sensibly by increasing the number of hydroxyls.…”
Section: Introductionmentioning
confidence: 99%